2015
DOI: 10.1080/17588928.2015.1053440
|View full text |Cite
|
Sign up to set email alerts
|

Embodied neural responses to others’ suffering

Abstract: To investigate whether and how facial mimicry in observers affects their empathic neural responses to others' pain expressions, we recorded event-related potentials (ERPs) from Chinese adults while viewing pain and neutral expressions of Asian and Caucasian faces. Facial mimicry was manipulated by allowing participants to freely move their facial muscles (the relaxed condition) or asking them to hold a pen horizontally using both teeth and lips to prevent facial muscle movement and facial mimicry (the blocked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 73 publications
(117 reference statements)
6
23
0
Order By: Relevance
“…1a ), The P2 amplitudes were enlarged by sadistic painful expressions compared with neutral expressions (ps < 0.001). These results replicated the previous ERP findings 25 , 26 and suggested that the frontal/central P2 amplitude was involved in coding emotional attributes (i.e., pain). Neither the main effect of genotype (F(2,92) = 0.29~1.19, ps = 0.28~0.60, η 2 = 0.006~0.03) nor its interaction with expression (F(2,92) = 0.11~0.89, ps = 0.42~0.90, η 2 = 0.00~0.02) was significant for the P2 amplitude, indicating that the OXTR genotype did not modulate the neural responses of the P2 amplitude to painful expression.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1a ), The P2 amplitudes were enlarged by sadistic painful expressions compared with neutral expressions (ps < 0.001). These results replicated the previous ERP findings 25 , 26 and suggested that the frontal/central P2 amplitude was involved in coding emotional attributes (i.e., pain). Neither the main effect of genotype (F(2,92) = 0.29~1.19, ps = 0.28~0.60, η 2 = 0.006~0.03) nor its interaction with expression (F(2,92) = 0.11~0.89, ps = 0.42~0.90, η 2 = 0.00~0.02) was significant for the P2 amplitude, indicating that the OXTR genotype did not modulate the neural responses of the P2 amplitude to painful expression.…”
Section: Resultssupporting
confidence: 90%
“…This approach allowed us to examine whether there is an association between OXTR rs53576 and empathic responses and whether this association is modulated by sadistic contexts. Empathic neural responses to others’ suffering were quantified by contrasting perceived painful vs. non-painful expressions, similar to the approach used in previous research 15 , 25 , 26 . Experiment 2 further investigated whether intranasal oxytocin interacts with social contexts to affect subjective empathic ratings and whether this sadistic context-dependent oxytocin effect is driven by enhanced empathic responses to painful expressions in sadistic contexts or decreased empathic responses to painful expressions in general contexts.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence that manipulation and voluntary changes in the contraction of facial musculature has a causal effect in the generation and/or recognition of emotional states and its neurophysiological correlates. As also explained in the psychological section above, intentional manipulation of facial musculature (e.g., asking participants to held a pen between the lips to inhibit smiling vs. held a pen between the teeth to facilitate smiling) causally affects how emotions in others are visually recognized (Adelmann and Zajonc, 1989;Buck, 1980;Han et al, 2016;Niedenthal et al, 2001;Niedenthal, 2007;Oberman et al, 2007;Strack et al, 1988;Zajonc, 1985). Hennenlotter and colleagues (2009), applied botulinum toxin (BTX) to the corrugator supercilii muscle to inhibit angry mimicry while participants viewed emotional faces.…”
Section: Neural Bases Of Mimicry and Yawn Contagionmentioning
confidence: 99%
“…The previous event-related potential studies of empathy demonstrated that empathy neural responses to perceived pain in others occur as early as 150 ms after stimulus onset (Fan and Han, 2008; Han et al , 2008, 2016; Decety et al , 2010; Li and Han, 2010; Sheng and Han, 2012; Sheng et al , 2016). The previous fMRI studies usually asked participants to make a response after the offset of visual stimuli and it usually took several hundreds of milliseconds for participants to take behavioral responses.…”
Section: Discussionmentioning
confidence: 97%